2021
DOI: 10.3390/su131810035
|View full text |Cite
|
Sign up to set email alerts
|

Stability Relevant Properties of an SiO2 Aerogel-Based Rendering and Its Application on Buildings

Abstract: Aerogel-based renderings and plasters have been spreading throughout Europe for nearly a decade. Several national and EU-funded projects have addressed this interesting building product, both at research level within academia and at application level within R&D of renowned industrial enterprises. At present, a number of investigations into the hygro-thermal, chemical and application properties of a commercially successful aerogel-based rendering and its main ingredient, SiO2 aerogel granules, have been und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, one could expect higher stresses than only one cycling to cause such level of deterioration. Additionally, the study presented by Stahl et al [ 2 ] showed that hydrophobized aerogel granules could resist harsh and alkali environments for longer periods without any sign of significant damage due to water intrusion inside the aerogel granules. As for the third explanation, the observations could also connect to the pore structure and moisture distribution in the samples before and after each wetting and drying cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one could expect higher stresses than only one cycling to cause such level of deterioration. Additionally, the study presented by Stahl et al [ 2 ] showed that hydrophobized aerogel granules could resist harsh and alkali environments for longer periods without any sign of significant damage due to water intrusion inside the aerogel granules. As for the third explanation, the observations could also connect to the pore structure and moisture distribution in the samples before and after each wetting and drying cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their superior thermal insulation properties, ACMs provide new technical solutions for the energy retrofitting of uninsulated building envelopes, particularly in listed and culturally valuable masonry buildings [ 1 , 2 , 3 ]. For many of the listed buildings, restrictions related to the preservation of character-defining elements, admissible thickness of building envelopes, and existing (moisture-related) damage to the construction, reduce the number of possible retrofitting measures [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent new use of silica aerogels is the creation of structured façades in historic buildings using silica aerogel renders [24,25]. This innovative approach demonstrates the versatility of such renders and their potential for reducing the energy demand of historic buildings without impacting their appearance if the existing render is not under heritage protection.…”
Section: Introductionmentioning
confidence: 99%
“…The most used type of aerogels, which have different types, is silica aerogels [36]. Silica aerogel, which is a nano structured material is a unique construction material with high porosity, ultra-low density and highly crossbound three dimensional webs, and consists of silica [37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Research on silica aerogel, which has lower heat conduction [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] when compared to other materials produced through complicated and expensive procedures [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], has proved that it has higher potential for thermal and acoustic insulation. Adding silica aerogel into construction materials can decrease their thermal conductivity or k-value significantly and result in thermal performance which was not previously possible [5].…”
Section: Introductionmentioning
confidence: 99%